2017
DOI: 10.1016/j.jare.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of moderate intensity aerobic exercise on chemotherapy-induced anemia in elderly women with breast cancer: A randomized controlled clinical trial

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Cancer-related fatigue is one of the most common symptoms during chemotherapy and is suggested to be influenced by many constitutional, clinical, and environmental factors in patients with PanCa. 81 There is no clear mechanistic explanation yet regarding the role of exercise in regulating CRF during active cancer treatment, although some reports suggest the possible association with improvements in chemotherapy-induced anemia 82 and cardiorespiratory capacity 83 after exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related fatigue is one of the most common symptoms during chemotherapy and is suggested to be influenced by many constitutional, clinical, and environmental factors in patients with PanCa. 81 There is no clear mechanistic explanation yet regarding the role of exercise in regulating CRF during active cancer treatment, although some reports suggest the possible association with improvements in chemotherapy-induced anemia 82 and cardiorespiratory capacity 83 after exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…An Egyptian (Mohamady, Elsisi and Aneis, 2017) group conducted a study in women with breast cancer (n=30, age 60-70) undergoing chemotherapy. The 12 week randomized intervention was an aerobic exercise (walking on a treadmill) 3 times per week for 25-40 min.…”
Section: Key Pointsmentioning
confidence: 99%
“…The endurance exercises helps to improves the growth hormone production through the hematopoiesis as well as enhance cytokines concentration which mature, proliferate and renew the blood stem cells. 22 Moreover, according to some previous literature, it has been concluded that aerobic training can significantly improve the Hb level.…”
Section: Resultsmentioning
confidence: 94%